2022
DOI: 10.3897/bdj.10.e81410
|View full text |Cite
|
Sign up to set email alerts
|

SLAM Project - Long Term Ecological Study of the Impacts of Climate Change in the Natural Forest of Azores: II - A survey of exotic arthropods in disturbed forest habitats

Abstract: The data we present consist of an inventory of exotic arthropods, potentially invasive, collected in exotic and mixed forests and disturbed native forest patches of the Azores Archipelago. The study was carried out between 2019 and 2020 in four islands: Corvo, Flores, Terceira and Santa Maria, where a total of 45 passive flight interception SLAM traps were deployed, during three to six consecutive months. This manuscript is the second contribution of the “SLAM Project - Long Term Ecological Study of the Impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…species composition, distribution of abundance) of the sampled communities. In two previous data papers, the project was described in detail and spider data were provided for several plots in Terceira and Pico Islands ( Costa and Borges 2021 ) and the occurrence of exotic and endemic arthropods in exotic and mixed forests and small disturbed remnants of native forests was also investigated ( Borges et al 2022 ).…”
Section: General Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…species composition, distribution of abundance) of the sampled communities. In two previous data papers, the project was described in detail and spider data were provided for several plots in Terceira and Pico Islands ( Costa and Borges 2021 ) and the occurrence of exotic and endemic arthropods in exotic and mixed forests and small disturbed remnants of native forests was also investigated ( Borges et al 2022 ).…”
Section: General Descriptionmentioning
confidence: 99%
“…Some studies revealed a higher species richness and abundance of arthropods in the forest edges, which could have implications on the re-colonisation of adjacent altered habitats (Jokimäki et al 1998, Magura 2002. Studies about Azorean arthropods have shown that the endemic species are mainly restricted to native forests and introduced species are more frequently detected in anthropogenic habitats, given their higher adaptability to the conditions of the newly-created habitat (Cardoso et al 2009, Florencio et al 2015. The impact of invasive plants species is the major threat to endemic and native species in the native forest areas (Borges et al 2019b) and their deleterious effects are probably more severe at the edges of the forests patches (Borges et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Borges et al (2022c) published an updated inventory of Staphylinidae of Azores, by collecting more than 10,000 records and identifying a total of 69 species (which represented 51% of the Staphylinidae known for the Archipelago), recording seven new Staphylinidae species for Azores and 66 new island records. In addition, recently two studies were published about Azorean arthropods including Staphylinidae : (1) Borges et al (2021) provided an inventory of arthropods collected in several Azorean agro-ecosystems, namely citrus orchards, maize fields and vineyards; and (2) Borges et al (2022e) published and inventory of Azorean arthropods, collected from different habitats types, such as exotic, mixed and native forest patches in four islands of the archipelago.…”
Section: Introductionmentioning
confidence: 99%
“…Given the taxonomic complexity of rove-beetles ( Coleoptera , Staphylinidae ), it is common that many collected individuals are misidentified or remain identified at genus or family level. In this study, we compiled all these records about Staphylinidae from three previous studies ( Borges et al 2021 , Borges et al 2022c , Borges et al 2022e ), that were posteriorly identified by expert Staphylinidae taxonomists. Consequently, this contribution has the main objective to provide the most updated inventory of Staphylinidae family ( Coleoptera , Insecta ) for the Azores, by including records collected between July 1999 and September 2020, in several habitat types of five islands of the Archipelago (Flores, Graciosa, Terceira, São Miguel and Santa Maria).…”
Section: Introductionmentioning
confidence: 99%